MHD boundary layer flow over a permeable flat plate in a ferrofluid with thermal radiation effect - Muhammad Khairul Anuar, Mohamed; Farah Nadia, Abas; Mohd Zuki, Salleh (IOP Publishing, 2019)
Adaptation from the thermal management with limited gravitational acceleration and excesses of radiation such as in aerospace, present study investigated the magnetohydrodynamic (MHD) boundary layer flow and heat transfer of ferrofluid past a permeable flat plate with thermal radiation effects. The mathematical model which is in non-linear partial differential equations are transformed to a more convenient form by similarity transformation approach before being solved numerically using the Runge-Kutta-Fehlberg (RKF45) method in MAPLE software. The characteristics and effects of pertinent parameters which are Prandtl number, magnetic parameter, thermal radiation parameter and the permeability parameter on the variation of Nusselt number and skin friction coefficient are analyzed and discussed. Three selected ferroparticles which are magnetite (Fe3O4), cobalt ferrite (CoFe2O4) and Mn-Zn ferrite (Mn-Zn Fe2O4) with water-based fluid are examined numerically.